Fe9S10-decorated N, S co-doped graphene as a new and efficient electrocatalyst for oxygen reduction and oxygen evolution reactions. Issue 5 (15th February 2017) - Ma, Xiu-Xiu; Su, Yan; He, Xing-Quan
Abstract : An advanced Fe9 S10 (700)/N, S-G catalyst for the oxygen reduction and evolution reactions was prepared via the combination of solvothermal and pyrolysis procedures. Abstract : Nowadays, the hybrids of non-precious metal nanocrystals and heteroatom-doped graphene have been intensively researched as efficient electrocatalysts for the oxygen reduction reaction (ORR) in energy conversion and storage. Herein, a novel hybrid comprising Fe9 S10 anchored onto nitrogen and sulfur dual-doped graphene (Fe9 S10 /N, S-G) was obtained via a two-step method, namely a π–π assemble process of p -phenyl-bis(3, 4-dicyanophenyl) thioether iron polyphthalocyanine (PTFePPc) and graphene oxide and a pyrolysis procedure. It is worth noting that the Fe9 S10 /N, S-G obtained at 700 °C facilitated a direct four-electron catalytic pathway toward ORR with a low yield of hydrogen peroxide, favored a quick kinetic process with a small Tafel slope of 49 mV dec −1 for its decent ORR activity, and achieved excellent operational stability in an alkaline medium. Furthermore, the proposed electrocatalyst also favored good OER performance, comparable with the benchmark RuO2 . The superior electrocatalytic activity of the composite is mainly attributed to the electronic coupling between nitrogen and sulfur atoms doped in the graphene, the highly active sites of Fe9 S10 and Fe–N, and the synergistic effects between Fe9 S10 and N, S-G.